Research on a Novel Combined Cooling and Power Scheme for LNG-Powered Ship - Xiu Xiao; Xiaoqing Xu; Zhe Wang; Chenxi Liu; Ying He (Journal of Marine Science and Engineering, 2023)
Cold energy recovery in LNG-powered vessels can not only improve the utilization efficiency of energy, but also benefit environmental protection. This paper put forward a new cascade scheme for utilizing flue gas waste heat and LNG cold energy comprehensively. The scheme was integrated by a dual organic Rankine circulation system (ORC), a high- and low-temperature cold storage system (TCS), an air conditioning system (ACS) and a seawater desalination system (SDS). The working medium of the dual ORC system was firstly determined by considering exergy efficiency and economic index simultaneously. On this basis, the adaptive weighted particle swarm optimization algorithm was employed to enhance thermodynamic performance of the scheme with the net output power as the optimization objective. The maximum net power and annual net interest rate can reach 725.78 kW and $115,300, respectively. Furthermore, the economic benefit of the scheme was analyzed by referring to the running track and the operation condition of the target ship. The results showed that the proposed scheme is a potential large-scale cryogenic technology and can bring considerable economic benefits to ship navigation.